Inheritance of salt tolerance in wild mungbean (Vigna radiata var. sublobata) - Deeroum, Artitaya; Thepphomwong, Khwanruedee; Laosatit, Kularb; Somta, Prakit (Agriculture and Natural Resources, 2024)
Importance of the work: Soil salinity is a major stress causing yield loss in crops. Wild progenitors and relatives of crops are reservoirs of genes conferring salt tolerance. The results from this investigation of the genetics of the salinity tolerance in a wild mungbean (Vigna radiata var. sublobata) should be useful in the breeding of salt-tolerance in mungbean. Objectives: To investigate the genetic control of salt tolerance in the wild mungbean accession CPI 100834. Materials & Methods: Cultivated mungbean (var. radiata) accession V2278AG (P1: salt-susceptible) and wild mungbean (var. sublobata) accession CPI 100834 (P2: salt-resistant) were used to develop F1 (P1 × P2), F2 (P1 × P2), BC1P1 [P1 × (P1 × P2)] and BC1P2 [P2 × (P1 × P2)] populations/generations. The six basic generations, (P1, P2, F1, F2, BC1P1 and BC1P2) were grown and evaluated for salinity tolerance at 75 mM NaCl using a hydroponic system. Segregation analysis, generation mean analysis and estimation of the number of effective factors (genes) were carried out. Results: The segregation analysis showed that salt tolerance was controlled by either one recessive gene or two genes with an inhibitory gene effect. The generation mean analysis and estimation of the number of effective factors consistently demonstrated that the tolerance was controlled by a single gene. Broad-sense heritability calculated for the salt-tolerance was moderate (47–49%). Altogether, these results indicated that the salinity tolerance of the wild mungbean CPI 100834 was controlled by a single gene. Main finding: The salt tolerance in the wild mungbean CPI 100834 appeared to be a quantitative trait controlled by a single gene.